Echinococcosis in humans and animals in Southern Africa Development Community countries: A systematic review - Miambo, R.D. (Food Waterborne Parasitol, 2020)
The taeniid Echinococcus is the causative agent of the zoonotic disease echinococcosis/hydatidosis and is associated with economic losses in livestock production. This review summarizes available scientific literature on circulating species of Echinococcus in humans, wild and domestic animals in countries of Southern Africa Development Community, and identifies knowledge gaps and recommend research priorities. Data were systematically accessed from Google Scholar, MEDLINE/PubMed and from library resources from December 2017 to June 2019. Meta-analysis was conducted in STATA program and heterogeneity and prevalence values were pooled by host species with 95% confidence interval. In intermediate hosts, the overall prevalence of Echinococcus by meat inspection was 10% (CI: 9–11%) in small ruminants, 7% (CI: 5–8%) in cattle, 1% (CI: 0–1%) in pigs and 9% (CI: 0–29%) in wild herbivores. In canids by CoproAg-ELISA and necropsy the prevalence was of 10% (CI: 8–10%) and 6% (CI: 3–10%) respectively. A high level of heterogeneity (I(2) > 65%) was observed for all study groups. Echinococcus equinus, E. canadensis, E ortleppi and E. felidis were reported from wildlife and E. ortleppi, E. granulosus s. s. and E. canadensis from humans. There is paucity of research in echinococcosis and gaps in prevalence reports over time in both humans and animals in the SADC region and we recommend an increase in future studies on the epidemiology of disease, risk factors for transmission in animals and humans and its relation with human health specially in the advent of HIV pandemic following a “One Health” approach.